Fertilizer and Soil Health in Africa Conference Presentations - Benson, Todd; De Weerdt, Joachim; Duchoslav, Jan; Masanjala, Winford; Ayalew, Hailemariam; Breisinger, Clemens; Karugia, Joseph T.; Kimaiyo, Faith Chepkemoi; Kimathi, Sally; Olwande, John; Nyondo, Christone J.; Nshakira-Rukundo, Emmanuel; et al. (CGIAR System Organization, 2024)
These collection of slides were presented by speakers at the Fertilizer and Soil Health in Africa - Research and Policy Conference, which took place on March 27, 2024, in Nairobi, Kenya. The conference was co-hosted by the CGIAR Research Initiatives on National Policies & Strategies (NPS) and Excellence in Agronomy (EiA).